Is an Ideal Sense of Humor Gendered? A Cross-National Study - Tosun, Sümeyra; Faghihi, Nafiseh; Vaid, Jyotsna (Frontiers in Psychology, 2018)
To explore lay conceptions of characteristics of an ideal sense of humor as embodied in a known individual, our study examined elicited written narratives by male and female participants from three different countries of origin: the United States, Iran, and Turkey. As reported in an earlier previous study with U.S.-based participants (Crawford and Gressley, 1991), our study also found that the embodiment of an ideal sense of humor was predominantly a male figure. This effect was more pronounced for male than for female participants but did not differ by country. Relative mention of specific humor characteristics differed by participant gender and by country of origin. Whereas all groups mentioned creativity most often as a component of an ideal sense of humor, this attribute was mentioned significantly more often by Americans than by the other two groups; hostility/sarcasm was also mentioned significantly more often by Americans than Turkish participants who mentioned it more often than Iranian participants. Caring was mentioned significantly more often by Americans and Iranians than by Turkish participants. These findings show a shared pattern of humor characteristics by gender but group differences in the relative prominence given to specific humor characteristics. Further work is needed to corroborate the group differences observed and to pinpoint their source.